Dynamic Desalination of Intruding Seawater After Construction of Cut-Off Walls in a Coastal Unconfined Aquifer - Zheng, Tianyuan; Gao, Mingpeng; Chang, Qinpeng; Zheng, Xilai; Walther, Marc (Frontiers in Marine Science, 2022)
Groundwater resources in coastal regions are under a constant threat of seawater intrusion. Using cut-off walls to prevent coastal groundwater deterioration are considered to be an effective countermeasure. After the construction of cut-off walls, a large amount of residual saltwater can be trapped in the landward aquifer. In this work we employ a field-scale numerical model to capture the dynamic behavior and the desalination process of the intruded seawater after the construction of the cut-off wall. The presented model is validated against a lab-scale experiment. Field-scale simulation reveal that a fast saltwater repulsion process proceeds within a short period (100 - 150 days), while it is found that the retreat of the residual saltwater wedge is rather slow at the beginning. This is because the desalination process always starts first in the vertical direction. Meanwhile, the saltwater area significantly increases in the downstream of the cut-off wall. The amount of residual saltwater after the construction of a cut-off wall mainly depends on the depth and hydraulic conductivity of the wall. The location of the wall only affects the retreat time. The removal of residual saltwater can be enhanced with the increase of the depth of the wall. However, a notable reduction in the desalination effectiveness is observed when the depth is beyond a certain value (25 m at the simulated scenarios). The desalination performance degrades dramatically when the hydraulic conductivity of the wall is higher than a certain threshold (8×10-7 m/s at the simulated cases). A near-complete removal of residual saltwater can be achieved within three years with suitable designs of the depth, location, and hydraulic conductivity of the cut-off wall.